Wireline Logging Data Interpretation on Coal Quality Value in The West Bangko Mining Area - Millenia, Tasya; Alimuddin, Alimuddin; Zulkarnain, DA; Wibowo, Rahmat Catur (Journal of Engineering and Scientific Research, 2025)
This study uses the well-logging method and the proximate values of laboratory test results at West Banko Pit 1 Mine, Lawang Kidul District, Muara Enim Regency, South Sumatra Province. The aim is to determine the relationship between the log density and coal quality. The proximate values used are the ash content, total moisture, and calorific value. This research used wellCAD software to interpret the coal seam in three wells: TM 01, TM 02, and TM 03. Meanwhile, a relationship between log density values and coal quality was identified using Microsoft Excel. From this research, it is found that there is a relationship between density and coal quality: the lower the density (g/cc), the better the coal quality.